2010
DOI: 10.4049/jimmunol.1001819
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of the Lectin Pathway of Complement with Phage Display Selected Peptides against Mannose-Binding Lectin-Associated Serine Protease (MASP)-1 and -2: Significant Contribution of MASP-1 to Lectin Pathway Activation

Abstract: The complement system, an essential part of the innate immune system, can be activated through three distinct routes: the classical, the alternative, and the lectin pathways. The contribution of individual activation pathways to different biological processes can be assessed by using pathway-selective inhibitors. In this paper, we report lectin pathway-specific short peptide inhibitors developed by phage display against mannose-binding lectin-associated serine proteases (MASPs), MASP-1 and MASP-2. On the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(108 citation statements)
references
References 67 publications
1
97
0
8
Order By: Relevance
“…Inhibitory Constant (K I ) Measurements-Equilibrium inhibitory constants of the SGMI variants listed in Table 1 were determined on MASP-1 and MASP-2 as described (8). Representative plots of K I measurements are shown in supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitory Constant (K I ) Measurements-Equilibrium inhibitory constants of the SGMI variants listed in Table 1 were determined on MASP-1 and MASP-2 as described (8). Representative plots of K I measurements are shown in supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…All these could be studied by selective inhibitors. In a recent paper we reported the first MASP-inhibitors developed by directed evolution of the 14-mer sunflower trypsin inhibitor (SFTI) (8). That study led to SFMI-1 (sunflower MASP inhibitor-1) and SFMI-2.…”
mentioning
confidence: 99%
“…An Arg-Ile bond is cleaved in the activation loop, which results in conformational change in the serine protease domain. Recently, we have shown that MASP-1, the most abundant protease component of the lectin pathway, controls lectin pathway activation Héja et al, 2012a;2012b;Kocsis et al, 2010;Megyeri et al, 2013). MASP-1 autoactivates and cleaves zymogen MASP-2, which then cleaves C4 and C2 components (Kidmose et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Combined, these data suggest that the MASPs have the ability to assemble in heterocomplexes and in that way contribute to a cross activation, as suggested by several recent papers (34)(35)(36)(37). In figure, we show a schematic overview of different combinations including both MASP homodimers (red/red or green/green protease domains in one dimer) and heterodimers (red/green).…”
Section: Discussionmentioning
confidence: 98%